2023
DOI: 10.1186/s13018-023-03786-6
|View full text |Cite
|
Sign up to set email alerts
|

Diacerein versus non-steroidal anti-inflammatory drugs in the treatment of knee osteoarthritis: a meta-analysis

Abstract: Background Knee osteoarthritis (KOA) is a common musculoskeletal condition affecting millions of people worldwide and posing a significant challenge to clinicians and researchers. Emerging evidence suggests that the multifaceted symptomatology of KOA may be alleviated by diacerein. With this in mind, we conducted a systematic review and meta-analysis to evaluate the efficacy and safety of diacerein in patients with KOA. Methods We systematically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the study revealed that diacerein outperformed NSAIDs in enhancing WOMAC and VAS scores during the follow-up period after the treatment, suggesting a stronger long-term effect. 19 KOA is predominantly characterized by cartilage degeneration, with pro-inflammatory cytokines playing a pivotal role in the development of the condition. 26 Diacerein, an anthraquinone derivative, functions by inhibiting the IL-1 system and its associated downstream signaling pathways, leading to the reduction of IL-1β activation and promoting cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study revealed that diacerein outperformed NSAIDs in enhancing WOMAC and VAS scores during the follow-up period after the treatment, suggesting a stronger long-term effect. 19 KOA is predominantly characterized by cartilage degeneration, with pro-inflammatory cytokines playing a pivotal role in the development of the condition. 26 Diacerein, an anthraquinone derivative, functions by inhibiting the IL-1 system and its associated downstream signaling pathways, leading to the reduction of IL-1β activation and promoting cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of adverse events associated with diacerein was similar to that of NSAIDs, indicating a favorable safety profile. 19 A study conducted a meta-analysis of the use of traditional Chinese herbal medicine in treating knee osteoarthritis patients. The analysis included 56 high-quality randomized controlled trials (RCTs) involving 5350 patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Several studies on the comparative efficacy, safety, and effects of diacerein and celecoxib on osteoarthritis have been published; the corresponding results indicated that diacerein is an effective treatment for osteoarthritis. [ 3 , 4 ] Nonetheless, in clinics, NSAID and diacerein combination therapy is frequently prescribed despite there being few studies comparing the efficacy and safety of NSAID and diacerein combination therapy. Additionally, the studies that have been conducted failed to include a placebo.…”
Section: Introductionmentioning
confidence: 99%